Upaya Peningkatan Nilai Produk Ikan Sidat melalui Partisipasi Masyarakat - Dina Muthmainnah; Ni Komang Suryati; Yenni Sri Mulyani (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Muthmainnah D, Suryati NK, Mulyani YS. 2020. Efforts to increase the value of anguillid eels products through community participation. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Anguillid eel is famous and as a luxury food, but Indonesian people's knowledge about this fish is still very limited. The study is based on public participation in answering questions posed through a questionnaire using the google form. The questionnaire was distributed by digital technology, namely the WhatsApp social media application platform. The intended respondents are aged 16 - 65 years and scattered throughout Indonesia. Data collection activity was carried out for three days in July 2020. The questionnaire was divided into nine questions, consisting of four general questions about respondents, and five questions regarding the respondent's knowledge of anguillid eel. The collected data were grouped based on the province of the respondent's domicile and age class. Data is displayed in tabulated form and description. The responses were selected based on a complete answer and got 1,100 respondents. The results showed that many Indonesian people are familiar with anguillid eel and know that it has high nutritional value. However, their interest in consuming it is relatively low because of the fish be like a snake. For this reason, the effort to increase food processing into a valuable product will facilitate marketing. It is hoped that the anguillid eel product will increase the selling value and the preference for consuming it.